Morphological diversity of Paramoeba perurans trophozoites and their interaction with Atlantic salmon, Salmo salar L., gills. Issue 9 (18th January 2016) - Wiik‐Nielsen, J; Mo, T A; Kolstad, H; Mohammad, S N; Hytterød, S; Powell, M D
Abstract: Amoebic gill disease (AGD) caused by the ectoparasite Paramoeba perurans affects several cultured marine fish species worldwide. In this study, the morphology and ultrastructure of P. perurans in vitro and in vivo was investigated using scanning and transmission electron microscopy (SEM and TEM, respectively). Amoebae cultures contained several different morphologies ranging from a distinct rounded cell structure and polymorphic cells with pseudopodia of different lengths and shapes. SEM studies of the gills of AGD‐affected Atlantic salmon, Salmo salar L., revealed the presence of enlarged swellings in affected gill filaments and fusion of adjacent lamellae. Spherical amoebae appeared to embed within the epithelium, and subsequently leave hemispherical indentations with visible fenestrations in the basolateral surface following their departure. These fenestrated structures corresponded to the presence of pseudopodia which could be seen by TEM to penetrate into the epithelium. The membrane–membrane interface contained an amorphous and slightly fibrous matrix. This suggests the existence of cellular glycocalyces and a role for extracellular products in mediating pathological changes in amoebic gill disease.